2022
DOI: 10.3389/fpsyg.2022.833028
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Work Practices and Employee Wellbeing—Does Health-Oriented Leadership Make a Difference?

Abstract: This paper sheds further light on the contextual boundaries in the relationship between high-performance work practices (HPWPs) and employee wellbeing. In particular, we analyze whether this relationship is moderated by health-oriented leadership behavior (i.e., staff care) which describes the extent to which leaders value, are aware of, and protect their followers’ health at work. Our analyses are based on employee data (N = 1,345) from Germany, covering two points in time. Findings show positive associations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…In our study TL did not interact with HPWS (post-hoc results not shown here). This is interesting in that other leadership styles ( Kalshoven and Boon, 2012 ; Salas-Vallina et al, 2020 ; Wang et al, 2021 ; Hauff et al, 2022a , b ) have been found to do that. Their interaction effects remains an important area of research, but so are their unique main effects as emphasized by our study, not least as the explanatory power of interaction effects tend to be marginal compared to the main effects, in particular when they are positive (e.g., Ehrnrooth et al, 2021 ; Hauff et al, 2022a , b ).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In our study TL did not interact with HPWS (post-hoc results not shown here). This is interesting in that other leadership styles ( Kalshoven and Boon, 2012 ; Salas-Vallina et al, 2020 ; Wang et al, 2021 ; Hauff et al, 2022a , b ) have been found to do that. Their interaction effects remains an important area of research, but so are their unique main effects as emphasized by our study, not least as the explanatory power of interaction effects tend to be marginal compared to the main effects, in particular when they are positive (e.g., Ehrnrooth et al, 2021 ; Hauff et al, 2022a , b ).…”
Section: Discussionmentioning
confidence: 81%
“…Similarly, other leadership researchers have argued that leadership and HRM represent distinct goal-directed influence processes, the important question being which of these inputs “do organizations need, and how do organizations develop and leverage the inputs for desired outcomes” ( Fischer et al, 2017 : 1,732). Research aiming to answer such questions with a focus on wellbeing is still very scarce ( Kalshoven and Boon, 2012 ; Jo et al, 2019 ; Salas-Vallina et al, 2020 ; Wang et al, 2021 ; Hauff et al, 2022a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the formalized training program in HRMPs, managers' facilitating collective learning behavior is a proximal determinant of employees' knowledge acquisition and sharing, which may decrease the effectiveness of HRMPs (Chuang et al, 2016). Additionally, based on conservation of resources theory (Hobfoll et al, 1991), HRM practices could substitute the effect of leadership on employee outcome (Hauff et al, 2022;Kalshoven and Boon, 2012).…”
Section: Combined Effects Of Leadership Styles and Hrm Practicesmentioning
confidence: 99%
“…Additionally, based on conservation of resources theory (Hobfoll et al. , 1991), HRM practices could substitute the effect of leadership on employee outcome (Hauff et al. , 2022; Kalshoven and Boon, 2012).…”
Section: Combined Effects Of Leadership Styles and Hrm Practicesmentioning
confidence: 99%
“…Complementing this evidence, specific measures of health-oriented leadership have been formulated to acknowledge the leadership–well-being link, for example, the health-oriented leadership concept by Franke et al (2014) . It describes a comprehensive framework of attitudes and action patterns of leaders that enhance employee well-being and has great leverage in the improvement and maintenance of employee well-being (e.g., Vonderlin et al, 2021 ; Hauff et al, 2022 ). Moreover, such health-specific leadership concepts have been shown to contribute to employee well-being above and beyond what is considered generally constructive leadership ( Gurt et al, 2011 ; Franke et al, 2014 ; Vincent-Höper and Stein, 2019 ; Kaluza et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%